The Central-American Situation on Globalization and Competitiveness (2015)
This document corresponds to an implementation in Globalization and Competitiveness, one of the classrooms of the Faculty of Economics at Institucion Universitaria Politecnico Grancolombiano, of the methodology developed under the research project: A divided Integration: An analysis of the implications for integration of the Latin American sub regional integration processes.